2006
DOI: 10.1111/j.1365-2524.2006.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing effective partnerships in older people's services

Abstract: The integration of older people's services is a challenge to all countries with an ageing population. Although it is widely acknowledged that acute care, long-term care, social care, housing, leisure, education and other services should all operate in a more 'joined-up manner', achieving this in practice remains extremely difficult. Against this background, the European Union (EU) Care and Management of Services for Older People in Europe Network (CARMEN) project set out to explore the management of integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…• the association of independently operating units (Nies, 2006;Ollonqvist et al, 2007) • voluntary participation in the network (Kaur, 2006) • the pursuit of joint or overriding objectives (Kodner, 2006;Montreuil and Garon, 2005) • the consistency of the processes (Piven et al, 2006;Rantz et al, 2004;Whitehead et al, 2001) • coordinated information management and DSS (Kodner, 2006;Lapane et al, 2006;O'Neil et al, 2004) • comparable documentation (Cavanagh, 2002;Mackenzie et al, 1998;Schnelle and Ouslander, 1997) • compatible technology (Kaushal et al, 2005;Schnelle et al, 2005;Scritchfield, 2007) • defined minimum data (Piven et al, 2006) • coordinated services planning (Caris-Verhallen and Kerkstra, 2001;Jacobs and Rummery, 2002;Lyons et al, 1995;Nies, 2006) • joint quality criteria (Grabowski et al, 2004;Hilliard, 2005;Rantz et al, 2000;Simmons et al, 2004;Stevenson, 2006;Zimmerman, 2003).…”
Section: Methods Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…• the association of independently operating units (Nies, 2006;Ollonqvist et al, 2007) • voluntary participation in the network (Kaur, 2006) • the pursuit of joint or overriding objectives (Kodner, 2006;Montreuil and Garon, 2005) • the consistency of the processes (Piven et al, 2006;Rantz et al, 2004;Whitehead et al, 2001) • coordinated information management and DSS (Kodner, 2006;Lapane et al, 2006;O'Neil et al, 2004) • comparable documentation (Cavanagh, 2002;Mackenzie et al, 1998;Schnelle and Ouslander, 1997) • compatible technology (Kaushal et al, 2005;Schnelle et al, 2005;Scritchfield, 2007) • defined minimum data (Piven et al, 2006) • coordinated services planning (Caris-Verhallen and Kerkstra, 2001;Jacobs and Rummery, 2002;Lyons et al, 1995;Nies, 2006) • joint quality criteria (Grabowski et al, 2004;Hilliard, 2005;Rantz et al, 2000;Simmons et al, 2004;Stevenson, 2006;Zimmerman, 2003).…”
Section: Methods Of Researchmentioning
confidence: 99%
“…At the functional level, however, it has to be concluded that standardisation has not been provided for to an extent that would constitute a criterion of efficiency -and therefore, also a functional criterion -of a long-term care network (Nies, 2006). Table 2 presents the aggregated interfering variables surveyed, those problem areas which influence the transfer process in view of the respective core process of the institutions involved.…”
Section: Statutory Structural Requirements and Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As already noted, achieving a genuine partnership is challenging due to a range of structural, cultural and organisational differences. The persistence of organisational and professional protectionism has blighted attempts to achieve integrated working (Glendinning, 2003;Nies, 2006). Partnerships are prone to break down over disputes about funding, priorities, management, and the design and delivery of services.…”
Section: Integrated Teamsmentioning
confidence: 99%
“…Moreover, research shows that the rise of integrated care teams did not necessarily result in a greater proportion of older people remaining living at home [19]. Barriers mentioned in the literature include cultural cleavages between professionals [12,20], interface problems between professionals and organisations [21], organisational and procedural rules and regulations prevailing in the sector [12,22], the supply-driven design of the system, the complexity of the system, financial and legislative problems [21], limited outside expertise and management capacity [23] and power relationships between newly integrated services and professionals [20].…”
Section: Introductionmentioning
confidence: 99%